Studi Efek Gangguan EMP (Elektromagnetic Pulse) pada Perangkat Elektronik - Jhav Sund Oktoricoento; Muhammad Ramdani; Sahrudin Sahrudin; Kun Fayakun; Harry Ramza; Akhiruddin Maddu (Prosiding Seminar Nasional Teknoka, 2018)
The existence of electronic devices in human life is very close today. Various areas of human life is always supported by electronic devices, ranging from the field of telecommunications to the security field, one of which is the surveillance system. Utilization of electronics in the military field is now known as Electronic Warfare (EW). One type of electronic attack is electromagnetic jamming. This study aims to examine the effect of EMP and determine the value of interference from the electromagnetic field to the surveillance system in the form of mini cameras. Variables in making measurements consist of source voltage, interference distance, and coil that each value is varied. Formulation of measurement data using Design Expert 11 with D-Optimal Response Surface method. The results showed that the maximum magnetic flux value generated by the signal jammer was 0,479 Wb / m2, the maximum interference value at the mini camera spectrum level was 2 dB, and the maximum interference value most often occurred at 4,9 MHz. The correlation coefficient value of the influence of the electromagnetic field on surveillance system between the predicted value of the simulation and the direct measurement value is -0,55093384.